2021
DOI: 10.3390/su14010196
|View full text |Cite
|
Sign up to set email alerts
|

Linking FDI and Sustainable Environment in EU Countries

Abstract: The aim of this study is to emphasize the link between the foreign direct investments (FDIs) and the sustainable environment in EU countries. We also focus on investigating the influence of other factors related to business environment on FDIs, considering the investors’ sustainable choice for the host countries, grouped according to FTSE Russell criteria. Using panel methodology and applying Ordinary Least Squares (OLS) method of data analysis, the authors reached the conclusion that a better-rated business e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 85 publications
(104 reference statements)
1
14
0
Order By: Relevance
“…Moreover, it allows the transfer of technologies, predominantly in the form of new capital diversities, which resultantly permits a country to invest in different R&D activities which ultimately promotes environmental sustainability. Findings are supported with past studies (Blanco et al, 2013;Fauzel, 2017;Jafri et al, 2021;Mukhtarov et al, 2021;Dornean et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, it allows the transfer of technologies, predominantly in the form of new capital diversities, which resultantly permits a country to invest in different R&D activities which ultimately promotes environmental sustainability. Findings are supported with past studies (Blanco et al, 2013;Fauzel, 2017;Jafri et al, 2021;Mukhtarov et al, 2021;Dornean et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…First, we observe that ED and ES are two distinct dimensions of EQ, thus, to the best of our knowledge, the focus of most of the researchers remains on ED, and the area of ES remains less focused on by prior researchers (Ganda, 2019;Ahmed et al, 2020). Second, we figure out that researchers are wrongly interpreting the impact of different factors on ES, as their findings are based on the explicit measures of environment quality, i.e., CO 2 or GHG emissions, which is not an appropriate measure of ES, instead it is an indicator of environmental pollution (Ahmed et al, 2020;Gu et al, 2020a;Gu et al, 2020b;Ali et al, 2021;Zhao et al, 2021;Dornean et al, 2022). Third, though the study believes that some attempts have been made by several researchers to scrutinize the role of FD in ES by using an appropriate proxy of ES (i.e., adjusted net savings), these studies are rare.…”
Section: Introductionmentioning
confidence: 89%
“…Based on previous literature reviewed, the model of this study was structured to investigate the impact of economic uncertainty, ecological footprint and bio capacity on foreign direct investment in South Africa. This research model is based on the framework posited by Chipalkatti et al (2021) which also guided the research of Dornean et al (2021). Their model includes the impact of environmental, governance, and macroeconomic factors on FDI inflows.…”
Section: Model Specificationmentioning
confidence: 99%
“…Nonetheless, Paul and Feliciano-Cestero (2021) indicated that the impact of FDI inflows on economic growth in different countries varies based on the level of its financial development. Furthermore, environmental, governance, institutional and economic factors have been noted to influence FDI and its ability to positively or negatively affect the productivity and development in a country (Chipalkatti et al, 2021; Dornean et al, 2021; Nguyen, 2017).…”
Section: Ecological Footprint and Foreign Direct Investmentmentioning
confidence: 99%
See 1 more Smart Citation